Reformulating the Law of ʿIddah in Indonesia: An Analysis of the Implementation of the Male ʿIddah Period under the Ministry of Religious Affairs Regulations in Banyumas Regency - Aqil, Ibnu (Lembaga Penelitian dan Pengabdian kepada Masyrakat, 2025)
This study seeks to examine the implementation of the male ʿiddah period as stipulated in the Circular Letter of the Director General of Islamic Community Guidance of the Ministry of Religious Affairs of the Republic of Indonesia (Number P-005/DJ.III/HK.00.7/10/2021), and to evaluate its relevance to gender equality and the reform of Islamic law in Indonesia. Employing a qualitative methodology with a juridical-empirical approach, the research connects normative legal provisions with practical field applications, complemented by a theological perspective to integrate empirical findings within the framework of Islamic thought. The analysis is further informed by Faqihuddin Abdul Kodir’s qirā’ah mubādalah theory and Nancy Fraser’s critical feminist theory. The findings reveal that the regulation of male ʿiddah constitutes a significant response to issues of gender equality and reflects efforts to modernize Islamic law in Indonesia. Field observations conducted at three Offices of Religious Affairs (KUA)—Gumelar, Lumbir, and Kembaran—in Banyumas Regency demonstrate that the regulation has been implemented, although variations in application, normative resistance, and socio-cultural challenges persist within the community. This study contributes to advancing the discourse on the reformulation of Islamic family law in Indonesia. The regulation concerning male ʿiddah not only provides novel insights for legal practice but also enhances the understanding of gender equality within the context of contemporary Islamic law.Abstrak: Penelitian ini bertujuan menganalisis penerapan masa iddah bagi laki-laki sebagaimana diatur dalam Surat Edaran Dirjen Bimas Islam Kementerian Agama Republik Indonesia Nomor P-005/DJ.III/HK.00.7/10/2021 serta menilai relevansinya terhadap kesetaraan gender dan pembaruan hukum Islam di Indonesia. Penelitian menggunakan metode kualitatif dengan pendekatan yuridis-empiris untuk menghubungkan antara ketentuan normatif dan praktik lapangan, serta pendekatan teologis untuk menjembatani temuan empiris dengan kerangka pemikiran Islam. Analisis diperkuat dengan teori qirā’ah mubādalah Faqihuddin Abdul Kodir dan feminisme kritis Nancy Fraser. Hasil penelitian menunjukkan bahwa pengaturan iddah bagi laki-laki merupakan bentuk respons kritis terhadap isu kesetaraan gender sekaligus upaya modernisasi hukum Islam di Indonesia. Temuan lapangan pada tiga kantor urusan agama (KUA) Gumelar, KUA Lumbir, dan KUA Kembaran di Kabupaten Banyumas menunjukkan bahwa regulasi tersebut telah diimplementasikan, meskipun masih terdapat variasi penerapan, resistensi normatif, dan tantangan sosial-kultural dalam masyarakat. Penelitian ini berimplikasi pada penguatan wacana reformulasi hukum keluarga Islam di Indonesia. Aturan tentang iddah laki-laki tidak hanya menawarkan wawasan baru dalam praksis hukum, tetapi juga berkontribusi pada perluasan pemahaman mengenai kesetaraan gender dalam konteks hukum Islam kontemporer.